Determinação de atividade de água, umidade e sal em peixes salgados e secos importados - Lima, Emanuel Joaquim Victória Monteiro Oliveira [UNESP]; Sant'Ana, Léa Silvia [UNESP] (Institute of Food Technology, 2011)
Brazil is a major importer in the world salted fish trade. The sale of these products must meet the established standards, based mainly on the salt and moisture levels. The aim of this study was to analyze the salt and moisture levels in imported Atlantic cod and Pacific cod, and in the dried salted fish Ling, Zarbo and Saithe, which are not classified as cod since they do not belong to the genus Gadus. The water activity was also analyzed, which could be a useful parameter to determine the quality of salted fish.The results showed that the legal limits for salt were much lower than the values found in the analyses. The moisture contents established for the category of salted fish, as determined by the Portuguese legislation, were more reliable. We suggest the inclusion of the water activity as a parameter for the evaluation of these products.

No comércio mundial de peixes salgados e secos, o Brasil é um dos principais importadores. A comercialização desse tipo de produto deve atender a determinados padrões, baseados principalmente nos níveis de sal e umidade. O objetivo deste estudo foi analisar os teores de umidade e sal em bacalhau do Atlântico, bacalhau do Pacífico e peixes salgados secos, Ling, Zarbo e Saithe importados, que, por não pertencerem ao gênero Gadus, não seriam classificados como bacalhau. Também foi analisada a atividade de água, que pode ser um parâmetro útil para determinar a qualidade dos produtos salgados. Os resultados mostraram que os limites legais de sal são muito inferiores aos valores encontrados nas análises. Os teores de umidade estabelecidos para categorias de salga, conforme determinado pela Legislação portuguesa, são mais confiáveis. Sugere-se a inclusão da atividade de água como parâmetro de avaliação destes produtos.
Water activity, moisture and salt levels in imported salted and dried fish
Keywords: Gadidae; Cod; Quality; Moisture; Sodium chloride; Water activity; Gadidae; Bacalhau; Qualidade; Umidade; Cloreto de sódio; Atividade de água